The effect of arrowroot diet on pancreatic and kidney histomorphology of mice induced by D-Galactose - Anindya Putri Aviciena; Fatya Auliya Hening I’tikafia; Muhammad Kharisma; Syaefuddin Ali Akhmad; Ika Fidianingsih (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Arrowroot contains antioxidants that can potentially reduce d-galactose-induced aging of the pancreas and kidneys. This study aimed to determine the effect of arrowroot administration on the histomorphology of the pancreas and kidneys of d-galactose-induced diabetic mice. Experimental research that was conducted in 2023 using Musculus Balb/C mice was divided into four groups as follows: a healthy control group (HC), negative control (NC) with d-galactose induction and standard feed, P1 and P2 groups with d-galactose induction, and 45% and 60% arrowroot feed. Histological slides were stained with hematoxylin and eosin. Data analysis was performed under a microscope at a magnification of 40 × 10. Severe signs of aging in the pancreas (cell atrophy, cytoplasmic vacuolation, necrosis, congestion, and inflammation) were observed in the NC and P1 groups and minimal signs were observed in the P2 group compared to the HC group, The damage mean (%) of tubular, glomerular kidney and inflammation scores were 52,46 ± 1,46, 76,66 ± 9,87, 67,99 ± 2,12, and 60,93 ± 0,55 (p=0,005); 62,64 ± 11,13, 70,48 ± 13,32, 71,25 ± 8,04, and 65,53 ±14,26, (p=0,707); 8,75 ± 2,5, 27,25 ± 4,57, 8 ± 7,25, and 13,5 ± 6,19, (p=0,001), respectively. In conclusion, administration of arrowroot affects the histomorphological features of the pancreas and kidneys of mice induced by aging using D-galactose.